2017
DOI: 10.1111/prd.12192
|View full text |Cite
|
Sign up to set email alerts
|

Dental geriatrics and periodontitis

Abstract: The present literature review is focused on two main areas: (i) periodontal conditions in older individuals; and (ii) the scientific data available on periodontal treatment outcomes in individuals ≥ 75 years of age. The population of older people is increasing but the data on periodontal therapies and their efficacy in this population are limited and need to be carefully reviewed. Although life expectancy has increased, this does not mean that older people are medically healthy. Several chronic systemic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 117 publications
0
24
0
3
Order By: Relevance
“…Among other symptoms, Type 2 diabetics can experience microvascular and vascular damage as well as an impaired wound healing. Patients are more susceptible to periodontitis and tooth loss (Persson, ). The main marker of glycemic control in diabetic patients is hemoglobin A 1C (HbA 1c ), and numerous studies identified in this review demonstrate that HbA 1c levels above 8% may result in reduced implant survival compared to lower levels.…”
Section: Discussionmentioning
confidence: 99%
“…Among other symptoms, Type 2 diabetics can experience microvascular and vascular damage as well as an impaired wound healing. Patients are more susceptible to periodontitis and tooth loss (Persson, ). The main marker of glycemic control in diabetic patients is hemoglobin A 1C (HbA 1c ), and numerous studies identified in this review demonstrate that HbA 1c levels above 8% may result in reduced implant survival compared to lower levels.…”
Section: Discussionmentioning
confidence: 99%
“…No such criterion of qualification for specialist periodontal treatment had been found in the available literature. However, this choice was driven by the desire to avoid measuring the position of the attachment in such a qualification, which at this age, regardless of periodontopathies, is moving apically, 22 which obviously may lead to an overestimation of therapeutic needs. In the 5-year cohort study, the most important risk factors for the progression of periodontitis in the 60-81 age group were identified -current nicotinism, elementary or secondary education, being single or divorced, and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal diseases continue to be a major public health problem worldwide, but there is evidence that the initiation, progression and severity does not affect all people in the same way (Dye, 2012;Petersen & Ogawa, 2012;Baelum & López, 2013;Persson, 2017). Some epidemiological studies have demonstrated that gingival inflammation affects 60 to 75% of pregnant women (Löe & Silness, 1963;Silness & Löe, 1964;Tilakaratne et al, 2000;Michalowicz et al, 2008;Ho & Chou, 2016), although not all present the same gingival inflammatory pattern and the symptoms can range from mild inflammation to severe hyperplasia, pain and profuse bleeding.…”
Section: Introductionmentioning
confidence: 99%